PRAKTIK PEMBERIAN MP-ASI TERHADAP RISIKO STUNTING PADA ANAK USIA 6-12 BULAN DI LOMBOK TENGAH [THE COMPLEMENTARY FEEDING PRACTICE AND RISK OF STUNTING AMONG CHILDREN AGED 6-12 MONTHS IN CENTRAL LOMBOK] - Ni Komang Ayu Swanitri Wangiyana; Titi Pambudi Karuniawaty; Ristania Ellya John; Ratu Missa Qurani; Jeslyn Tengkawan; Ayu Anandhika Septisari; Zulfikar Ihyauddin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2020)
ABSTRACT Improper complementary feeding practice practice is one of the problems that often occurs in developing countries. This problem can lead to inadequate nutrient intake, especially protein intake which is associated with physical growth problems in children under five years, including stunting. This study was an observational analytic study with a cross-sectional design which aims to determine the association between complementary feeding practice and stunting incidence among children aged 6-12 months in Central Lombok. A total of 206 children with a mean age of 9,3 months was selected for this study by cluster sampling. Most of them were female. In this study, we analyzed 4 parameters of complementary feeding practice, namely age of indroduction of complementary foods, texture of complementary foods given, frequency of complementary feeding, and amount of complementary foods given. This study found that there was a significant association between frequency of complementary feeding (p = 0.047, 95% CI) and amount of complementary foods given (p = 0.020, 95% CI) with stunting incidence. Meanwhile, other parameters namely age of indroduction of complementary food and texture of complementary foods given did not have a significant association with stunting incidence. Keywords: complementary feeding practice, short stature, stunting ABSTRAK Praktik pemberian makanan pendamping ASI (MPASI) yang tidak tepat merupakan salah satu masalah yang sering terjadi di negara berkembang. Hal tersebut dapat menyebabkan asupan zat gizi yang tidak adekuat, terutama dari protein yang berhubungan dengan masalah gangguan pertumbuhan fisik pada anak balita, termasuk stunting. Penelitian ini merupakan penelitian analitik observasional dengan rancangan cross-sectional yang bertujuan untuk mengetahui hubungan praktik pemberian MPASI terhadap kejadian stunting pada anak usia 6-12 bulan di Lombok Tengah. Sebanyak 206 anak dengan rerata usia 9,3 bulan terpolih menjadi subjek penelitian ini menggunakan cluster sampling. Sebagian besar berjenis kelamin perempuan. Pada penelitian ini, kami menganalisa 4 parameter praktik pemberian MPASI, yaitu usia pertama mendapatkan MPASI, bentuk MPASI yang diberikan, frekuensi MPASI, dan jumlah MPASI yang diberikan. Penelitian ini menemukan adanya hubungan yang signifikan antara frekuensi MPASI (p=0,047, 95% CI) dan jumlah MPASI yang diberikan (p=0,020, 95% CI) dengan kejadian stunting pada anak. Sedangkan parameter lainnya seperti usia memulai MPASI dan tekstur MPASI, tidak memiliki hubungan yang signifikan terhadap kejadian stunting. Kata Kunci: perawakan pendek, praktik pemberian MPASI, stunting